CORPORATE SOCIAL RESPONSIBILITY AND ORGANIZATIONAL RESILIENCE IN CONSTRUCTION COMPANIES RIVERS STATE, NIGERIA. (Journal of the Management Sciences, 2024)
This study examined corporate social responsibility and organizational resilience in construction companies Rivers State, Nigeria. The researcher formulated three objectives and tested the three hypotheses. A descriptive survey was adopted and population of thestudy was 151 employees selected from seven construction companies in Rivers State, Nigeria. The researcher used random sampling technique and Taro Yamane’s formula to determine the sample size which was 110. Both Primary and secondary data were utilized for the study through a structured questionnaire. Spearman rank correlation was used to test the hypotheses and descriptive statistics applied for the analysis of research questions. The findings discovered a positive significant relationship between workforce-related corporate social responsibility and innovativeness. The researcher concluded that work environment-related corporate social responsibility influences growth strategy. It wasrecommended that construction companies should use workforce-related corporate social responsibility as organizational culture by training employees to acquire competent skills and knowledge to achieve innovativeness.
Keywords: : Corporate social responsibility, workforce, organizational resilience.